AN AUTOPSY BASED CROSS-SECTIONAL STUDY ON ISOLATED LIVER INJURIES FROM FATAL ROAD TRAFFIC ACCIDENTS ATTENDING A TERTIARY CARE MEDICAL INSTITUTE (Journal of Forensic Medicine & Toxicology, 2023)
Background: In today’s era of machines road traffic fatalities are an unfortunate common occurrence. One of the causes of such deaths are injuries to the liver. The present study aims to find the prevalence of isolated liver injuries from fatal road traffic incidents and the factors affecting these incidents. Materials and Methods: A prospective cross sectional study on the victims of Road Traffic Accident (RTA) brought for medico-legal autopsy was done for a period of 1 year. Results: Out of total 176 cases of RTA, 38 cases were included in the study based on the findings. The highest of 22 cases (44.74%) were in the 21-30 age group, with motor vehicle (2-wheeler) being the most common vehicle. Males were most frequently involved. The driver of vehicle (50%) cases was the highest involved; generally, patients survived for a mean duration of 2-6 hours. Most of the victims didn’t use seat belts. Conclusion: The victims were mostly males involved without wearing a seatbelt and the survival period was low but prompt intervention went a long way in saving the life of the victim.
Keywords: Road traffic fatalities; Liver injury; Seat belts; Motor vehicle